Plasma Brain-Derived Neurotrophic Factor as a Peripheral Marker for the Action Mechanism of Antidepressants - Lee, Hwa-Young; Kim, Yong-Ku (Neuropsychobiology, 2008)
Numerous studies have demonstrated that depression is associated with a decreased expression of brain-derived neurotrophic factor (BDNF). BDNF shows antidepressant-like effects in animal models. Therefore, we tested the hypothesis that BDNF might be a peripheral marker for the mechanism of action of antidepressant agents in humans. Thirty-two patients meeting the DSM-IV criteria for major depressive disorder and 50 normal control subjects were recruited for this study. Plasma BDNF levels and Hamilton Depression Rating Scales were measured at baseline and 6 weeks after antidepressant administration. At baseline, the mean plasma BDNF level was lower in the depressive patients (698.1 ± 537.7 pg/ml) than in the control subjects (830.7 ± 624.8 pg/ml), although the difference was not statistically significant (p = 0.33). The plasma BDNF levels in depressive patients significantly increased from 698.1 ± 537.7 to 1,028.9 ± 744.5 after 6 weeks of antidepressant treatment (p = 0.01). Moreover, plasma BDNF levels were significantly increased after 6 weeks of treatment in the responder group, while there was no statistically significant change in the unresponsive group. These results suggest that the therapeutic response after antidepressant administration might be attributable to the increase in BDNF levels. BDNF may play a critical role in the action mechanism of antidepressant drugs. Further studies with a larger number of subjects are needed to verify these findings.